A equação que identifica o gráfico da figura abaixo é dado por:
a) f (x) = x2 + 2x + 3
b) f (x) = - x2 - 2x - 3
c) f (x) = - x2 + 2x - 3
d) f (x) = - x2 - 2x + 3
e) f (x) = - x2 + 2x + 3
Anexos:
![](https://pt-static.z-dn.net/files/d98/81a9c3609f1718e4476a4cc7665a29f2.jpg)
Soluções para a tarefa
Respondido por
5
e)
Explicação passo-a-passo:
........................
Anexos:
![](https://pt-static.z-dn.net/files/dfb/fa6f52f09a959bf3f175a45a04fb4abc.jpg)
![](https://pt-static.z-dn.net/files/dff/8faf4bcf3d7c0f74203b42284b4839a4.jpg)
Perguntas interessantes
Português,
10 meses atrás
História,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
1 ano atrás
Química,
1 ano atrás